THE EFFECTIVENESS OF ULTRASOUND IN THE DIAGNOSIS OF CHOLECYSTITIS - Malokhat M. Jumaeva; Dilnoza A. Khasanova (Central Asian Journal of Medicine, 2023)
The use of ultrasound for cholecystitis makes it possible to make a correct diagnosis in the shortest possible time, determine subsequent treatment tactics, and promptly begin conservative or surgical treatment. Timely diagnosis of damage to the gallbladder and bile ducts, congestion of the extrahepatic and intrahepatic bile ducts. The creation of laboratory panels to assess the severity and severity of the pathological process during exacerbation of chronic or latent forms of this disease is important. Acute cholecystitis is one of the most significant acute diseases of the abdominal organs.